Guia de livros didáticos de língua portuguesa dos anos finais do ensino fundamental: análise da rede discursiva - Silva, Lívia Aparecida da (2023)
In the Guidelines for Didactic books of Brazilian Portuguese for the elementary school latest years: an assessment of discursive formations, it is analyzed the statements as presented in the 2020 Guidelines for Didactic books of Brazilian Portuguese Language for the elementary school latest years. Therefore, the statements of this Guide are consolidated as the body of this research and their underlying speeches as its object of study. In this study, the underlying discursive formations of the Guideline are analyzed, as well as the power and knowledge dynamics objectifying the Portuguese language teacher of elementary school latest years; it was verified the subjects speaking through the Guide and their position; the most recurrent discourses emerging in the statements constituting the Guide were also identified; it is shown which discursive and non-discursive practices the principles and criteria established in the 2020 Guide are related with; it is also addressed the discursive regularities that prevailed in relation to the first textbook legislation in 1938 and it was verified the contributions of the Guide to the formation of the Portuguese language teacher. This research used the Discourse Analysis of French origin as support, prioritizing mainly foucaultian studies (1979, 2000, 2003, 2004, 2005, 2008) on discourse and its materiality, the utterance, as well as the relations of knowledge, power and truth it is constituted of. The history of textbook policy was also referred, especially the one addressed by Costa et. al. (1987) and Bomeny et. al. (1984) and the first legislation of Brazil Textbook, Decree-Law No. 1006 of December 1938. This is a qualitative study based on a documentary analysis, (Cellard, 2012; Le Goff,1996; Foucault, 2008) considering the document seen as a monument. Thus, it was possible to verify that the Guide is constituted by a discursive formation involving discursive practices ( stemming from the statements of Legislation, Guidelines, Official Norms, Decree-Law related to Education) and non-discursive practices (involving the State, under represented by MEC, with PNLD, with co-participation of Federal Universities, state and municipal education networks and civil society institutions). Discourses of knowledge, authority, punishment, direction, prescription, standardization, among others, were manifested in the statements constituting the Guide. The criteria of the Guide are linked to a broad discursive formation that involves the official Standards of Education and various segments of society. The standardization and the way of turning the Guide public are among some discursive regularities that have been observed. The subjects who speak in the Guide were authorized to address the Portuguese language teachers working in the classroom. The Guide contributes to the education of the Portuguese language teacher as it presents to individuals information on how the process of choosing the textbook takes place.